Species Composition of Main Pests of Fig and Bioecology of Important Species - Sh.Q. Yuldasheva; S. Nosirova (Zien Journals, 2024)
The climatic conditions of Uzbekistan are favorable for the cultivation of crops adapted to the subtropical climate. These include figs. These tree-shrubs have been planted since ancient times and have become a branch of horticulture for the countries of Central Asia, including the people of Uzbekistan.
Keywords: fig; climate; crops; cultivation